'Write your biggest dream on a sheet of paper and burn it': subjectivity and subjectification in becoming Israeli - Vale de Almeida, M. (2019)
This article focuses on the processes of subjectivity change and subjectification among Brazilian Jews who become citizens of Israel. Global Zionist movements and the State of Israel interpellate their Brazilian and Jewish Diasporic identities, and the process of migration (aliyah) is rooted in diverse motivations, that are further challenged by the political situation in Israel/Palestine. The characteristics of the Jewish Diaspora and of citizenship accession in Israel allow for different ways of looking at contemporary migrations and circulations of people, as well as the way that national and cultural identifications are negotiated between subjects, social context, and the state.